Paddy Growers’ Knowledge of Soil Health Card in North Coastal Region of Andhra Pradesh (Indian Journal of Extension Education, 2024)
Paddy cultivation demands site-specific care from transplanting to post-harvest. Soil health cards offer farmers insights for effective fertilizer use, tailored to their soil’s condition. The research was led in the years 2023-2024 to know knowledge of soil health card by paddy growers in the north coastal of Andhra Pradesh. Samples were collected from six mandals across Rajam, Therlam, Bobbili from Vizianagaram district, and Ponduru, Hiramandalam, and Ecterla from Srikakulam district, totalling 180 respondents from 12 villages. Some Paddy growers have a comprehensive knowledge of SHCs and their importance in enhancing soil health and crop productivity, while others have limited awareness or misunderstandings. The research highlights obstacles to the utilization of SHCs, such as insufficient means of communication, and doubts regarding the effectiveness of SHCs. Findings revealed that the majority of respondents displayed a medium level of knowledge that is (45.00%) followed by paddy growers with low levels (27.77%) and (27.33%) paddy growers had a high level of knowledge about soil health cards.